The royal hunt of the sun - Shaffer, Peter 1926-2016 (Pegasus Entertainment, 2007)
The Spanish explorer Pizarro captures the Inca god-chief Atahualpa and promises to free him upon the deliverance of a horde of gold. But Pizarro finds himself torn between his desire for conquest and his sense of honor after friendship and respect develops between captive and captor
Original: USA/Großbritannien, 1969
Keywords: Feature films; Film; DVD-Video